A modeling study of sessile water droplet on the cold plate surface during freezing under natural convection with gravity effect considered. (October 2021) - Menglong, LU; Mengjie, Song; Zhenjun, MA; Xiaotao, Wang; Long, Zhang
Abstract: Freezing of water droplet is widely seen and important in the fields of aerospace, cold energy storage, and power production. To investigate the freezing process of a sessile water droplet on a horizontal cold plate, a theoretical model was developed. Different from previously reported models, the effects of supercooling and gravity on the physical properties and the water droplet profile are both considered, respectively. This model is validated with the experimental data of two parameters, including the freezing time and the freezing front radius. The results indicate that the deviation of freezing time is decreased from 7.69% to 0.17%, while the accuracy improved by 7.52%. The average deviation of the freezing front radius is decreased from 142.90 μm to 57.94 μm, with the accuracy improved by 59.46%. At the freezing stage, the appearance of the dynamic growth angle contributes to the less deviation of the freezing front radius. The eccentricity of droplet shape decreases from 0.45 to 0.03, with the eccentricity decreased by 93.45%. The temperature change rates inside a droplet show a gradually decreasing tendency, and the temperatures at different droplet locations present different limiting values. The findings of this study are beneficial for understanding droplet solidification process as well as new technologies for refrigeration, deicing, and defrosting.